UGT2B15 single nucleotide polymorphism reduces dabigatran acylglucuronide formation in humans - Park, Jin-Woo; Kim, Jong-Min; Bang, Young Yoon; Kim, Kyoung-Ah; Yu, Sungwook; Park, Ji-Young (Frontiers in Pharmacology, 2025)
BackgroundDabigatran etexilate (DABE), a prodrug of dabigatran (DAB), is a direct thrombin inhibitor used to prevent ischemic stroke and thromboembolism during atrial fibrillation. The effect of genetic polymorphisms on its metabolism, particularly UGT2B15, has not been extensively explored in humans. This study aimed to investigate the effects of UGT2B15, ABCB1, and CES1 polymorphisms on the pharmacokinetics of DAB and its acylglucuronide metabolites in healthy subjects.MethodsA total of 124 healthy males were genotyped for UGT2B15, ABCB1, and CES1 polymorphisms. After a single 150 mg dose of DABE, plasma concentrations of total and free DAB, as well as dabigatran acylglucuronide (DABG) were measured using LC-MS/MS. Pharmacokinetic parameters were analyzed using non-compartmental methods, and statistical comparisons were conducted between the genotype groups.ResultsUGT2B15 c.253G>T significantly affected free DAB pharmacokinetics, with a lower Tmax and oral clearance in TT genotype (n = 28, p < 0.05). For DABG, Cmax was significantly higher in GG genotypes (n = 32, 42.3 ± 16.3 ng/mL) compared to that in GT (n = 64, 32.4 ± 20.5 ng/mL) and TT (29.7 ± 17.1 ng/mL) genotypes. Similarly, the AUCall of DABG was highest in GG genotypes (327 ± 148.3 ng h·mL-1), followed by GT (238.7 ± 166.5 ng h·mL-1) and TT (223.3 ± 165.4 ng h·mL-1) genotypes (p < 0.05). The metabolite-to-parent ratios (m/p ratios) for Cmax and AUCall were significantly higher in GG and GT genotypes than that in TT genotype. ABCB1 and CES1 polymorphisms had no significant impact on the pharmacokinetics of DAB or DABG.ConclusionUGT2B15 polymorphisms were associated with difference in DAB glucuronidation and pharmacokinetics in healthy male participants.